Foreign exchange rationing, wheat markets and food security in Ethiopia - Dorosh, Paul A.; Ahmed, Hashim A. (International Food Policy Research Institute, 2009)
Beginning in April 2008, lack of access to foreign exchange effectively stopped private sector wheat imports. Government imports and subsidized sales to millers and households in late 2008, subsequently increased domestic supply and lowered market wheat prices, though market prices remained above import parity levels. Allowing the private sector access to foreign exchange for wheat imports (or auctioning government wheat imports of the same volume) would have eliminated the wheat import subsidy, estimated at about $US 90 million in 2008, while reducing market prices to import parity levels.